2019
DOI: 10.1055/a-0871-6831
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Vitamin D Deficiency Status and PCOS in Infertile Women?

Abstract: Introduction It is still unclear in the literature whether low vitamin D levels play a role in the pathogenesis of polycystic ovary syndrome (PCOS), especially with respect to the regulation of anti-Müllerian hormone (AMH). Therefore, we aimed to investigate whether there could be a relationship between vitamin D deficiency status and PCOS. Materials and Methods A total of 146 infertile women were divided into two groups according to their ovarian reserve patterns: (i) normal (NOR), and (ii) high (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
1
13
1
4
Order By: Relevance
“…Interestingly, the study found an association between VDR polymorphisms and AMH levels in PCOS women, while there was no correlation between AMH and AMHR-II gene polymorphisms and AMH levels [52]. Arslan et al [53] similarly found no correlation between serum AMH and 25OH-D levels in PCOS patients (r = 0.027, p = 0.836) and control individuals (r = −0.112, p = 0.307). This study included 146 Turkish infertile women that were divided into normal ovarian reserve patterns (n = 86) and PCOS ovarian reserve patterns (n = 60).…”
Section: Observational Studiesmentioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, the study found an association between VDR polymorphisms and AMH levels in PCOS women, while there was no correlation between AMH and AMHR-II gene polymorphisms and AMH levels [52]. Arslan et al [53] similarly found no correlation between serum AMH and 25OH-D levels in PCOS patients (r = 0.027, p = 0.836) and control individuals (r = −0.112, p = 0.307). This study included 146 Turkish infertile women that were divided into normal ovarian reserve patterns (n = 86) and PCOS ovarian reserve patterns (n = 60).…”
Section: Observational Studiesmentioning
confidence: 84%
“…The current systematic review included eighteen cross-sectional studies and six interventional studies assessing the relationship between serum vitamin D levels and serum AMH levels. The cross-sectional studies demonstrated conflicting results, with several studies finding a positive correlation between serum AMH and vitamin D levels [42,46,50,61], while most studies reported largely negative findings [43][44][45]47,49,[51][52][53][54][55][56][57][58][59]. The systematic review and meta-analysis of the interventional studies revealed that vitamin D supplementations affect serum AMH levels but have opposite effects depending on the ovulatory statuses of the women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У той же час дефіцит 25(OH)D та гени пов'язані з низьким рівнем вітаміну мають незначний вплив на індекс маси тіла (ІМТ) [10]. З огляду на високий рівень ожиріння серед жінок зі СПКЯ і той факт, що в загальній популяції низька концентрація вітаміну D була пов'язана з ожирінням, незалежну роль вітаміну D при наявності СПКЯ оцінити складно [11].…”
Section: клінічна ендокринологіяunclassified
“…Отримані результати свідчать про існування взаємозв'язку між вітаміном D і ІМТ у жінок зі СПКЯ та узгоджуються з іншими дослідженнями [11]. Відомо, що ожиріння може сприяти зниженню рівня циркулюючого вітаміну D, затримуючи вітамін D в жирових тканинах.…”
Section: результати та їх обговоренняunclassified